Semiannual Kelvin Waves Propagation along the South Coast of Sumatra-Jawa-Bali and the Lesser Sunda Islands Observed by TOPEX/POSEIDON and ERS-1/2 Satellites - F. Syamsudin (Institute for Research and Community Services, Institut Teknologi Bandung, 2004)
The merged TOPEX/POSEIDON (T/P) and ERS-1/2 altimeter data during 10/14/1993